Kadar Protein Pada Tempe Bersumber Dari Kacang Kedelai Hasil Perendaman Bonggol Nanas (Ananas comosus (Linn) Merrill) - Yenni Aulia Putri; Elita Agustina; Ria Ceriana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Pineapple is one of the fruits consumed by the community. Pineapple produces waste in the form of pineapple weevils which are thrown away for nothing. Pineapple weevil can be used as a medium for soaking soybeans in the process of making tempeh. The purpose of this study was to determine the effect of pineapple weevils to increase tempeh protein content, to determine the duration of soaking soybeans in pineapple cone juice which was effective in increasing tempeh protein content, and to determine the feasibility of a reference from the results of research on the effect of soaking soybean seeds in pineapple weevil juice to increase protein content in tempe. The research design used was a completely randomized design (CRD) with 6 treatments and 4 replications, namely P1 (5 hours of immersion), P2 (6 hours of immersion), P3 (7 hours of immersion), P4 (8 hours of immersion), P5 (9 hours of immersion). ) in pineapple weevil juice, and P0 (12 hours of immersion in distilled water as a control). Protein content testing was carried out using the Kjeldahl method through a process of digestion, distillation, and titration carried out at the Goods Quality Testing and Certification Center (BPSMB). Analysis of the protein content data obtained used the ANOVA method and carried out the BNJ further test. The results of data analysis showed an increase in protein content in tempeh soaked with pineapple weevil juice at P1 of 17.39% and showed that the most effective soaking time was 5 hours in pineapple weevil juice